Synthesis of high-purity, layered structured K2Ta4O11 intermediate phase nanocrystals for photocatalytic water splitting. Issue 37 (15th July 2016) - Wang, Ping; Sun, Feng; Kim, Jin Hyun; Kim, Ju Hun; Yang, JunHe; Wang, XianYing; Lee, Jae Sung
Abstract : New high-purity kalitantite intermediate phase with a layered structure for photocatalytic water splitting. Abstract : High-purity K2 Ta4 O11 (kalitantite) intermediate phase with a layered structure, as a new family member of alkali-metal tantalate semiconductors, was successfully prepared via a simple and cost-effective flux growth technique using potassium chloride (KCl) at a low temperature of 800 °C for only 4 h. The as-synthesized K2 Ta4 O11 was characterized by XRD, SEM, TEM, STEM/EDS, and UV-Vis DRS, etc. It was found that the K2 Ta4 O11 single nanocrystals were non-stoichiometric in the size range of 100–500 nm, and the indirect band gap of K2 Ta4 O11 was correctly determined to be 4.15 eV. The K2 Ta4 O11 not only exhibited a high and stable photocatalytic H2 generation rate of ∼45.3 μmol h −1 g −1 in an aqueous methanolic solution with the photodeposition of Pt as co-catalysts, but also possessed the photocatalytic ability for simultaneous evolution of H2 and O2 in a stoichiometric ratio, with loading of NiO particles as cocatalysts. Thus, it can be mainly attributed to the benefits of KCl flux lowing the reaction temperature, and increasing the surface area and crystallinity of K2 Ta4 O11, that the charge efficiency and enhancement of the photoreactivity for water splitting are improved.